Short‐term ecological and behavioural responses of Mediterranean ant species Aphaenogaster gibbosa (Latr. 1798) to wildfire. Issue 5 (25th January 2013) - Lázaro‐González, Alba; Arnan, Xavier; Boulay, Raphael; Cerdá, Xim; Rodrigo, Anselm; Leather, Simon R.; Christie, Fiona
Abstract Fire greatly affects plant and animal biodiversity. There is an extensive body of literature on the effects of fire on insect communities, in which a large variability of responses has been observed. Very few studies, however, have addressed functional responses at the species level, information that would greatly enhance our understanding of the impact of fire at higher organisational levels. The aim of this study is to analyse the short‐term ecological and behavioural responses of the Mediterranean ant Aphaenogaster gibbosa to fire‐induced environmental changes. We compared aspects of the abiotic and biotic environment relevant to this species, as well as differences in colony foraging behaviour, on unburnt and burnt plots in a Mediterranean area that was affected by a wildfire. Our results showed that fire modified plant cover around nests and daily cycles of soil temperature close to the nest. Although there were no significant differences in food quantity, food quality (particularly seed composition) was different between unburnt and burnt plots. In accordance with these environmental changes, we found significant differences in the daily activity rhythms and diet composition of A. gibbosa between unburnt and burnt plots. Overall, these differences did not result in significant changes in overall foraging activity and efficiency, allowing ant colonies to maintain the same food intake regardless of the habitat they occupied. We conclude that A. gibbosa uses behavioural plasticity to modify its foraging strategy in recently burnt environments and thus survive post‐fire conditions.